Bank management and financial services - Rose, Peter S. (McGraw-Hill, 2005)
The banking industry affects the welfare of every other industry and the economy. Banks are the leaders of the financial-services industry as a whole, however, financial-service competitors are now challenging them more than ever before. Bank Management and Financial Services is designed to help students master established management principles and to confront the perplexing issues of risk, regulation, technology, and competition that bankers and other financial-service managers see as their greatest challenges for the future.